Investing in agrochemicals in the cocoa sector of Côte d’Ivoire: hypotheses, evidence and policy implications - Keho, Y.; Gockowski, J.; David, S. (2007)
This paper presents empirical evidence to show how socioeconomic factors affect the adoption of and investment in agrochemicals in the cocoa sector of Côte d’Ivoire. The analysis uses primary farm-level data collected in 2002 from a nationally representative sample of more than one thousand cocoa farmers. The study describes the status of the adoption of various chemical inputs and uses a multiplicative heteroscedastic Tobit model to identify and quantify the impact of the socioeconomic environment on the incentive to invest. The results generally show that farmer, household and village characteristics are all important in explaining the farmers’ decisions. The paper concludes by outlining a number of implications for strategic targeting of farmers and locations. These should serve as entry points for a successful diffusion of efficient pest, disease and soil management programs.